PELATIHAN PEMBUATAN MEDIA INTERAKTIF BERBASIS MODEL DEEP LEARNING PENDIDIK DI SEKOLAH DASAR - Susandi, Ari; Ahmad Ipmawan Kharisma; Rizka Novi Irmaningrum; Oriza Zativalen (ALAINA: Jurnal Pengabdian Masyarakat, 2025)
The community service program that we are conducting aims to train the creativity of elementary school educators in the Babat Lamongan elementary and secondary education environment through the creation of interactive media. The methods used are the planning stage, the implementation stage and the evaluation stage. Based on the results of the activity, it shows that all educators can follow and create interactive media based on the deep learning model in PKM activities with full creativity and enthusiasm. Interactive media based on the deep learning model can be one of the media for educators to tell and explain their ideas in the learning process. Through this interactive media, students can develop their writing skills and through this interactive media. The process of creating interactive media based on the deep learning model certainly also involves digital sources to create real concepts, of course this can help students improve their writing and speaking skills. The success and creativity of educators in the Babat Lamongan elementary and secondary education environment in creating unique and reactive interactive media as a whole, this activity can be a valuable media to support the writing and speaking skills of students at the elementary school level to the maximum.